Revisiting The Effects of Corporate Social Responsibility on Financial Perfomance: Organizational Culture as a Moderating Variable - Ardiniamalia, Utari; Ghofar, Abdul; Andayani, Wuryan (Universitas Negeri Malang, 2023)
This research aims to examine the influence of corporate social responsibility on financial performance and explore the effect of organizational culture as a moderating variable. This research uses a sample of banking companies listed on the Indonesia Stock Exchange in 2017-2021. Measuring corporate social responsibility uses content analysis with the help of a checklist. Financial performance is measured using return on assets (ROA). Testing in this research uses multiple regression methods and moderated regression analysis (MRA). Based on the purposive sampling method, 105 observations were obtained during the research period. The research results show that corporate social responsibility does not affect financial performance. Clan, adhocracy, and hierarchy cultures strengthen the relationship between corporate social responsibility and financial performance. Market culture does not enhance the relationship between corporate social responsibility and financial performance.